AIAA Guidance, Navigation, and Control Conference 2012
DOI: 10.2514/6.2012-4816
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Contrail Reduction Strategies Based on Aircraft Flight Distances

Abstract: This paper evaluates a set of contrail reduction strategies based on the flight range of aircraft as contrail reduction strategies have different impacts on aircraft depending on how they plan to fly. In general, aircraft with longer flight distances cruise at the altitudes where contrails are more likely to form. The concept of the contrail frequency index is used to quantify contrail impacts. The strategy for reducing the persistent contrail formation is to minimize the contrail frequency index by altering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Literature about mitigating aviation-induced contrails revealed that several simulation tools were used to analyse the vertical displacement of flight paths to avoid PCFA [5,34,[39][40][41][42]. Research indicated that the aircraft could change the flight altitude or re-route to reduce contrail formation [30][31][32]35,43].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Literature about mitigating aviation-induced contrails revealed that several simulation tools were used to analyse the vertical displacement of flight paths to avoid PCFA [5,34,[39][40][41][42]. Research indicated that the aircraft could change the flight altitude or re-route to reduce contrail formation [30][31][32]35,43].…”
Section: Figurementioning
confidence: 99%
“…A multi-objective mathematical optimisation problem is proposed, based on which the potential trade-off between several performance indicators is analysed in detail. The Pareto frontier in multi-objective functions corresponded to the different assignments Literature about mitigating aviation-induced contrails revealed that several simulation tools were used to analyse the vertical displacement of flight paths to avoid PCFA [5,34,[39][40][41][42]. Research indicated that the aircraft could change the flight altitude or re-route to reduce contrail formation [30][31][32]35,43].…”
Section: Figurementioning
confidence: 99%
“…Soler et al proposed a method for calculating the cost of the contrail [12]. Chen et al developed a strategy to reduce the contrail based on environment and operational cost, linking CO 2 emission and contrail formation to environmental cost through changes of absolute global temperature potential (AGTP) [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Chen, Sridhar, Li and Ng evaluated the contrail reduction strategies based on aircraft travel distances. 14 Sridhar, Ng and Chen integrated emission and climate models together with air traffic simulations to further understand the complex interaction between the physical climate system, emissions and air traffic. 15 They analyzed the trade-offs between extra fuel burn and reduction of global surface temperature change.…”
Section: Introductionmentioning
confidence: 99%